Orality in the civil process - Cayllahua Peña, Máximo Javier (2019)
Any reform in the justice system will have a transitional period, in which new models and procedural mechanisms will be revived, attitudes and new conduct in oral litigation will be adapted that will not only result in the success of the claim and protection of rights, but will make the process more agile, fast, transparent and effective, as is the case with the pilot plan implemented in the Superior Court of Justice of Arequipa, and it is through process management by audiences that the current system of the written process is being changed.